Muhammad Islam's first great general - Gabriel, Richard A. (Campaigns and commanders, 2007)
That Muhammad succeeded as a prophet is undeniable; a prominent military historian now suggests that he might not have done so had he not also been a great soldier. Best known as the founder of a major religion, Muhammad was also Islam's first great general. While there have been numerous accounts of Muhammad the Prophet, this is the first military